Comorbidities affect risk of nonvariceal upper gastrointestinal bleeding - Crooks, Colin John; West, Joe; Card, Timothy R. (WB Saunders, 2013)
Background & Aims The incidence of upper gastrointestinal bleeding (GIB) has not been reduced despite the decreasing incidence of peptic ulcers, strategies to eradicate Helicobacter pylori infection, and prophylaxis against ulceration from nonsteroidal anti-inflammatory drugs. Other factors might therefore be involved in the pathogenesis of GIB. Patients with GIB have increasing nongastrointestinal comorbidity, so we investigated whether comorbidity itself increased the risk of GIB.